Highly excited states for the helium atom in the hyperspherical adiabatic approach - De Groote, J. J. [UNESP]; Masili, M.; Hornos, J. E. (IOP Publishing, 1998)
The hyperspherical adiabatic approach is used to obtain the highly excited series 1sns 1S e and 1s(n + 1)p 1P o of the helium atom. The introduction of appropriate asymptotic conditions at large values of the hyperspherical radius results in a stable algorithm that allows the calculation of the full atomic spectrum with precision of a few parts per million. Comparison with the variational calculations available in the literature shows that the accuracy of the results improves with increasing principal quantum number. We present the energies up to n = 31 which is the typical value used in multiphoton excitation experiments.
Keywords: Algorithms; Atomic spectroscopy; Computer simulation; Electron energy levels; Helium; Excited states; Quantum theory